Tribal and subtribal relationship of Epidendroideae Lindl. (Orchidaceae) with emphasis on Epidendreae Humb., Bonpl. & Kunth based on matK gene - Kułak, Magdalena; Górniak, Marcin; Romowicz, Agnieszka (Biodiversity: Research and Conservation, 2006)
The Epidendroideae (Orchidaceae) is one of the orchids largest subfamilies with substantially larger number of genera and species than all other subfamilies altogether. Taxa incorporated in the subfamily Epidendroideae are characterized by the largest variety and diversity of forms. Once in a while, the classification inside the Epidendroideae subfamily undergoes modifications. It is because different scientists base their classification system on different features. This paper shows is to show relationship between genera within the subfamily Epidendroideae (with the particular consideration of the tribes Dendrobieae and Epidendreae) on the basis of the analysis of the nucleotide sequence matK gene.